PENGARUH DEBIT ALIRAN TERHADAP SEDIMENTASI DI SUNGAI LEMATANG KABUPATEN LAHAT - Sri Martini, RA; Bahri, Zainul; Miranda, Ade Tricia (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2020)
Sedimentation that occurred in the Lematang River in Lahat Regency was caused by river bank erosion, construction activities, and household waste brought by the flow discharge. The flow of the Lematang river will certainly affect the amount of sedimentation that will occur in the Lematang river.Based on the test results of the analysis of sediment sample filters, the results obtained d50 = 0.425 mm, and the results of research on the river cross-section with the aim to calculate the volume of base sediment sediment / bed load that occurs by flowing Lematang river flow obtained H = 0.41 m, B = 0 , 41 m, V = 2,650 m / sec.Based on the results of the analysis of the influence of flow discharge on sedimentation in the Lematang River, Lahat Regency, it is known that the type of bed load sediment in the Lematang River is poorly graded sand with large sediment transport carried by the flow discharge in the study segment of 0.022 (m3 / sec) with the duboy's method and 0.0000004 (kg / sec / m) with the shield's method, so the sediment volume for the next one year is 693,792 (m3 / sec) m for the duboy's method and 126,144 (kg / sec / m) for the shield's method .